Sesamum indicum Oleosin L improves oil packaging in Nicotiana benthamiana leaves. (6th September 2021) - Yee, Suyan; Rolland, Vivien; Reynolds, Kyle B.; Shrestha, Pushkar; Ma, Lina; Singh, Surinder P.; Vanhercke, Thomas; Petrie, James R.; El Tahchy, Anna
Abstract: Plant oil production has been increasing continuously in the past decade. There has been significant investment in the production of high biomass plants with elevated oil content. We recently showed that the expression of Arabidopsis thaliana WRI1 and DGAT1 genes increase oil content by up to 15% in leaf dry weight tissue. However, triacylglycerols in leaf tissue are subject to degradation during senescence. In order to better package the oil, we expressed a series of lipid droplet proteins isolated from bacterial and plant sources in Nicotiana benthamiana leaf tissue. We observed further increases in leaf oil content of up to 2.3‐fold when we co‐expressed Sesamum indicum Oleosin L with At WRI1 and At DGAT1. Biochemical assays and lipid droplet visualization with confocal microscopy confirmed the increase in oil content and revealed a significant change in the size and abundance of lipid droplets.